Evaluation of temperature rises during the application of different power levels of potassium titanyl phosphate and neodymium-doped:yttrium aluminum garnet lasers to external primary root canals - Recai Zan; Ihsan Hubbezoglu; Murat Unal (Elsevier, 2016)
Background/purpose: Nowadays, laser systems play crucial roles in endodontic treatments. Therefore, these systems should be investigated in terms of parameters that may prevent periodontal tissues damages during laser irradiation. In this context, the purpose of this study was to evaluate temperature rises during the application of different power levels of potassium titanyl phosphate (KTP) and neodymium-doped:yttrium aluminum garnet (Nd:YAG) lasers to external primary root canals. Materials and methods: Sixty primary mandibular molars were selected and chemomechanical preparation was performed. KTP laser treatment was applied to 30 of these 60 samples and the remaining 30 received Nd:YAG laser treatment. The teeth samples received laser application (KTP or Nd:YAG) at three different power levels (1 W, 1.5 W, and 2 W, respectively, applied to 10 samples from each group). Nine holes were drilled (1 mm in diameter) through the level of the coronal, middle, and apical third of each tooth canal to provide entry for a Type L thermocouple wire, which was used to measure temperature changes. Data were assessed with two-way analysis of variance and the Tukey test. Results: All power levels indicated statistically significant differences between Nd:YAG and KTP laser systems (P < 0.05). Moreover, the same regional (apical, middle, and coronal) comparisons performed between Nd:YAG and KTP laser systems showed statistically significant differences (P < 0.05). Conclusion: All parameters of KTP laser indicated lower temperature rises than Nd:YAG laser. Therefore, KTP laser may be preferable to protect the periodontal tissues from harmful thermal effects during the endodontic treatment of primary root canals.